1894 Ala. Laws 616, ch. 345 - (:unkn) unknown (General Publisher, 1894)
Approved the town of Columbia to require licensing but also placed a maximum license fee of one hundred dollars on dealers of pistols, pistol cartridges, bowie knives, dirk knives.Gun shops, or gun repair shops capped at five dollars.
--
Keywords: LICENSE - DEALERS